Pt(IV) Complexes with Biologically Active and Physicochemical Properties Modifier Ligands - Aher, Sainath; Zhu, Jinhua; Liu, Xiuhua; Borse, Laxmikant (Current Bioactive Compounds, 2024)
The octahedral Pt(IV) complexes contain either inert or biologically active ligands where the nature of these axial ligands provides additional stability and synergistic biological activity. There are many literature reports from each of the classes mentioning the varied nature of these axial ligands. The targeting, as well as the non-targeting nature of these moieties, exerts additive or synergistic effects of anticancer activity of Pt(II) moieties. Herein, we have discussed the effects of these axially oriented ligands, changes in the non-leaving am(m)ine groups, and changes in the leaving groups on the biological activity. In this review, we have discussed the axial ligands with a focus on the nature of the ligands and alterations in biological activities.
Keywords: cancer cell lines